A ruptured blister aneurysm of the A1 segment of the anterior cerebral artery with communicating hydrocephalus: a case report with histo-pathological and genetic predisposition - Sundip Charmode; Mehul Kaliya; Tarang Patel; Simmi Mehra (AOSIS, 2023)
Background: Cerebral arteries experience aneurysms more commonly than systemic arteries. This case report discusses a blister aneurysm that affected the anterior cerebral artery's A1 segment. The histological and genetic background is related to the aneurysm's unique presentation. Case description: The blister aneurysm ruptured, leading to interventricular and basal subarachnoid hemorrhage. A right sided fronto-temporo-parietal decompressive craniotomy was performed to explore it, along which clipping operation was performed. A communicative hydrocephalus develops after the craniectomy for which a right parietal VP shunt was conducted that underwent malfunction. The patient succumbed due to septic shock after 4 months of VP shunt revision surgery. Discussion: Different forms of cerebral aneurysms were analyzed, with regards to their histo-pathological characteristics and underlying anatomical basis of their formation. Finally, the genetic propensity of all the aneurysm was explained. There was an interventricular and basal subarachnoid hemorrhage because of the blister aneurysm's rupture. To explore it, a fronto-temporo-parietal decompressive craniotomy on the right side was done, along with a clipping operation. After the craniectomy, a right parietal VP shunt was performed, however it malfunctioned, leading to a communicative hydrocephalus. After undergoing VP shunt revision surgery for 4 months, the patient passed away from septic shock. Conclusions: The common types of cerebral aneurysms (saccular, fusiform, mycotic and blister) and the anatomical basis of their occurrence are reviewed in-depth in the histopathological and genetic literature.